Volatile oil composition and antioxidant activity of leaf of Chaerophyllum villosum Wall. ex DC from Uttrakhand, India - Joshi, Rakesh Kumar; Mathela, C S (Recent Research in Science and Technology, 2013)
The genus Chaerophyllum, belonging to Apiaceae family, comprised of about 110 species which includes annual and perennial herbal plants widely distributed in temperate and sub temperate zones of Asia, Africa and Europe. Chaerophyllum villosum Wall. ex DC. was widely distributed in E. Asia Himalayas from India to Bhutan, Nepal and China and widely grows in moist shady places, road sides or open grassy places at elevations of 2100-3500 m. In high altitude tribes of Uttarakhand Himalaya (India) it was commonly known and sold in the name of ‘Ganjari’ widely used by people in food, spice and also as medicine. The volatile oil composition of leaf of Chaerophyllum villosum Wall. ex DC. (family: Apiaceae) were analyzed and compared using capillary GC and GC-MS. The leaf essential oil of C. villosum was dominated by monoterpene hydrocarbons (91.34%) represented by γ-terpinene (74.93%) as single major constituent followed by p-cymene (10.00%), terpinolene (2.93%) and β-pinene (2.54%), the antioxidant activity of leaf essential oil also evaluated.